Determination of acetonitrile and cyanide in rat blood: Application to an experimental study - Mateus, Fabiano Henrique; Lepera, José Salvador [UNESP]; Lanchote, Vera Lucia (My University, 2005)
Methods were developed for the analysis of acetonitrile and its metabolite cyanide in the blood of rats exposed to acetonitrile. Acetonitrile was analyzed by the headspace technique coupled to gas chromatography with detection by flame ionization, and cyanide was analyzed by high-performance liquid chromatography with fluorescence detection (λ ex = 418 nm and λ em = 460 nm) after derivatization of the ion with naphthalene 2,3-dicarboxyaldehyde and taurine. The quantitation limits of the methods for the analysis of acetonitrile and cyanide were 4.875 μg/mL and 0.025 μg/mL, respectively. The coefficients of variation of 10% or less obtained for intra- and interassay precision indicate the precision of these analytical methods and the systematic errors, all less than 5%, indicate that the methods are quite accurate. The methods were applied to an experimental study after the animals received acetonitrile at the doses of 2 mmol/kg or 5 mmol/kg.
Keywords: 2,3 naphthalenedicarboxaldehyde; acetonitrile; cyanide; ion; taurine; accuracy; analytic method; animal experiment; blood examination; controlled study; derivatization; fluorescence; gas chromatography; high performance liquid chromatography; male; nonhuman; rat; Acetonitriles; Animals; Chromatography, High Pressure Liquid; Cyanides; Flame Ionization; Male; Rats; Rats, Wistar; Reproducibility of Results